Newly identified poor prognostic factors for adult T-cell leukemia–lymphoma treated with allogeneic hematopoietic stem cell transplantation. Issue 1 (2nd January 2017) - Tokunaga, Masahito; Uto, Hirofumi; Takeuchi, Shogo; Nakano, Nobuaki; Kubota, Ayumu; Tokunaga, Mayumi; Takatsuka, Yoshifusa; Seto, Masao; Ido, Akio; Utsunomiya, Atae
Abstract: To explore pre-transplantation prognostic factors for adult T-cell leukemia-lymphoma (ATL), we retrospectively analyzed allogeneic hematopoietic stem cell transplantation (allo-HSCT) in 70 patients at our institute (63 acute type and seven lymphoma type patients). Forty-five patients died after HSCT and the three-year overall survival (OS) rate was 35.2%. By univariate analysis, the adverse prognostic factors for OS were performance status ≥2, hematopoietic cell transplantation-specific comorbidity index (HCT-CI) score ≥3, European Group for Blood and Marrow Transplantation (EBMT) risk score ≥5, HSCT from an HLA-mismatched donor, serum soluble interleukin-2 receptor (sIL-2R) level ≥10, 000 U/mL, lymphocyte count ≥4000/μL, and hemoglobin <9 g/dL at the time of HSCT. EBMT risk score and sIL-2R were identified as significant adverse prognostic factors using multivariate analysis. This analysis clearly demonstrates for the first time that HCT-CI and EBMT risk scores are reliable prognostic factors for ATL patients receiving allo-HSCT.